Towards structure determination of the hepatitis C virus p7 protein - Haddad, Lisette (University of Ottawa (Canada), 2008)
The hepatitis C virus (HCV) affects 3% of the world's population and is a major cause of liver cirrhosis and cancer. The p7 protein of HCV has recently gained much attention due, in part, to its essential role in viral infectivity. This small integral membrane protein containing two transmembrane helices is thought to perform this function by forming a heptameric cation-specific ion channel. In order to gain insight into its channel function I have initiated nuclear magnetic resonance (NMR) experiments that can start to reveal the structure of this protein. For this purpose a C-terminally His6-tagged p7 was expressed in E. coli as a C-terminal fusion protein to glutathione-S-transferase (GST). This fusion protein was purified under denaturing conditions using nickel affinity chromatography and cleaved using thrombin to separate p7 from GST. Greater than 90% pure His-tagged p7 was obtained using reversed-phase high-performance liquid chromatography. 15N, 13C-labeled samples were reconstituted in detergent solutions to allow analysis by solution NMR. A limited series of sample optimization experiments were performed to identify conditions that would give rise to folded p7 in a detergent-micelle complex that would be amenable for chemical shift assignment. Of the conditions tested, p7 solubilized in the lysophospholipid LMPG at 40°C was found to give rise to the most favorable spectrum with a chemical shift dispersion indicative of a helical protein. A suite of three-dimensional triple resonance experiments were then performed and assignment of backbone chemical shifts was initiated. Based on these experiments it was possible to make preliminary chemical shift assignments for over half of the observed resonances. Secondary chemical shift calculations performed with these chemical shifts are consistent with expectations for alpha-helical structure in the TM segments. These results also show that p7 possesses a third helix outside of the putative TM segments. This structure may be important for the proposed genotype-specific function of this part of p7. Overall, the development of protocols to obtain isotope-labeled p7 samples, along with the initiation of NMR analysis, has opened the door to the ultimate goal of p7 structure determination.
Keywords: Chemistry, Biochemistry.